2021
DOI: 10.2147/jir.s307801
|View full text |Cite
|
Sign up to set email alerts
|

The ACE2-Ang-(1‑7)-Mas Axis Modulates M1/M2 Macrophage Polarization to Relieve CLP-Induced Inflammation via TLR4-Mediated NF-кb and MAPK Pathways

Abstract: has been identified as an important anti-inflammatory and anti-fibrotic factor. This study determined how the ACE2-Ang-(1-7)-Mas axis affected M1/ M2 macrophage polarization and thus contributed to anti-inflammatory processes in the cecal ligation and puncture (CLP)-induced inflammation model. Materials and Methods: ELISA, western blotting, and qRT-PCR were used to verify that Ang-(1-7) decreased the expression of pro-inflammatory cytokines and increased anti-inflammatory cytokines. The differentiation of M1/M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 26 publications
1
36
1
2
Order By: Relevance
“…The JNK pathway was reported to be essential for M1 macrophage polarization in HFD-fed mice, and lack of JNK decreases the expression of M1 phenotypic related genes and increased the M2 related genes in adipose tissue macrophages. 37 Furthermore, NF-κB pathway was also reported to be associated with pCRPinduced M1 macrophage polarization, 38 however, inhibition of NF-κB activation by its inhibitor had no effect on the production of mCRP-induced M1-related cytokines in our study. Therefore, our results may suggest that although mCRP was the monomeric form of CRP, they shared different signaling pathways in showing the M1 macrophage polarization bias.…”
Section: Discussioncontrasting
confidence: 60%
“…The JNK pathway was reported to be essential for M1 macrophage polarization in HFD-fed mice, and lack of JNK decreases the expression of M1 phenotypic related genes and increased the M2 related genes in adipose tissue macrophages. 37 Furthermore, NF-κB pathway was also reported to be associated with pCRPinduced M1 macrophage polarization, 38 however, inhibition of NF-κB activation by its inhibitor had no effect on the production of mCRP-induced M1-related cytokines in our study. Therefore, our results may suggest that although mCRP was the monomeric form of CRP, they shared different signaling pathways in showing the M1 macrophage polarization bias.…”
Section: Discussioncontrasting
confidence: 60%
“…Another study conducted by Collins et al showed that Ang-(1-7) could affect RAW 264.7 cells by inhibiting TNF-α production in a dose-dependent manner [33]. These results were supported by several other studies [34][35][36][37], and were consistent with the decreased plasma Studies regarding the role of the RAS system in sepsis have also shown that Ang-(1-7) could attenuate the AngII-stimulated enhancement in lipid peroxidation and reduce the superoxide dismutase activity in murine hearts [38]. It was previously reported that Ang-(1-7) could stimulate protein kinase A (PKA) production via the activation of MasR, which was followed by an enhanced calcium current in the heart.…”
Section: Discussionmentioning
confidence: 57%
“…Previous researches have confirmed the anti-inflammatory role of ACE2 via its enzymatic product Ang-1–7 [ 43 , 44 ]. Anti-inflammatory drugs such as COX2 inhibitors exhibits exciting effects on synergistically enhancing the efficacy of immunotherapy [ 45 ].…”
Section: Discussionmentioning
confidence: 97%